O papel de Zaratustra na filosofia de Nietzsche: do meio-dia ao grande meio-dia - Mignoni, Neomar Sandro (2015)
This is an investigation of the role played by the character of Zarathustra in the context of the mature Nietzsche's work, especially with regard to noon and the great noon. Recognizing that the late period of Nietzsche's philosophy is marked by the affirmative proposal of a revaluation of all values, this study is dedicated to understand the journey crossed by the character in relation to the noon as the beginning of the character s task and the great noon as a celebration of the incorporation of the eternal recurrence of the same and the final consummation of the revaluation of all values. In light of this, the first section seeks to demonstrate the Nietzschean critique of Western culture, marked by nihilism and death of God such as it appears in the Twilight of the Idols under the heading How the 'true world' finally became the fable . Following this thought, we seek to understand the noon time while the total elimination of dualities and also the man's reconciliation with the nature. From this point the task of Zarathustra begins. Then, analyzing the works of the second period of Nietzsche's philosophy, the following section reconstructs the ground from which Zarathustra and the noon s philosophy develop themselves. This undertaking is intended to make known the character and his task from the context of the revaluation of all the values. Finally, in the third and final section, after accompanying the trajectory of Zarathustra along the prologue of the homonymous work to get the event of noon, the research follows the character in the path of his going under [Untergang], showing thus its incorporation of the eternal recurrence and the consolidation of the unconditional affirmation of the amor fati existence. When dealing with Zarathustra maturation, that allows him from towards the celebration of the great noon, this dissertation ends by calling attention to the role that the disciples of Zoroaster, while philosophers of the future, play in the realization of the revaluation of all the values.